MORPHOGENESIS OF RISSOIDAE IN THE INLAND BASINS OF THE EASTERN PARATETHYS - Iljina L.B. (My University, 2006)
Miocene rissoids from the heterochronous low-salinity seas of the Eastern Paratethys (Early Chokrakian, Karaganian, Late Konkian, Early Sarmatian, and Early Maeotian) were revised. The polyphyletic genus Mohrensternia is subdivided into several generic and subgeneric taxa. The new genus Zhgentia and the new subgenera Rissoa (Turboellina), R. (Pseudoturboellina), and R. (Maeotia) are established.
Keywords: Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен